Harmonia jako strategia w tworzeniu substantywno-substantywnych konstrukcji łącznikowych (na przykładzie nazw osobowych) - Bortnowska, Paulina (Studia Rossica Posnaniensia, 2016)
Using the structure of hyphenated compound words has become a productive way of creating new nominations in contemporary Russian. The aim of this article is to show that harmony as an orderly combination of elements in a whole is the main concept that underpins multiple psycholinguistic processes, resulting in the occurrence of hyphenated compound words in Russian speakers’ language.